Correlação entre os parâmetros de virulência e resistência ao antimonial trivalente (SbIII) em isolados clínicos de Leishmania (Viannia) braziliensis - Cordeiro, Laísa Vilar (2017)
Treatment with antimonials has several limitations, among them the progressive emergence of parasites resistant to these drugs. In this situation, recent evidence suggests that the parameters antimonial resistance and virulence may be correlated in Leishmania sp. have been published in the literature. In this context, this work aimed to investigate whether there is a correlation between virulence and resistance to trivalent antimonial (SbIII) from two clinical isolates of Leishmania (Viannia) braziliensis, named AF and JCTS. Promastigote forms of these parasites resistant to SbIII were selected, obtaining cultures with a resistance level corresponding to 14 and 13 times the wild-type IC50 (sensitive to SbIII) for the isolates AF and JCTS, respectively. When analyzing the stability of the phenotype of acquired resistance, it was verified that both clinical isolates presented an unstable profile, with progressive reversion of resistance after successive passages in drug absence. In morphological analysis, it was observed that two cultures resistant to SbIII presented higher amount of promastigote forms with metacyclic characteristics when compared to sensitive cultures. However, the growth in culture medium was similar for sensitive and resistant cultures of both clinical isolates. In stationary phase of growth, the percentage of serum that caused 50% of cellular lysis (EC50) of the AF culture sensitive to SbIII was 2.3%, whereas the corresponding drug resistant culture presented EC50 9.4%. Similarly, the sensitive and SbIII resistant JCTS cultures showed EC50 2.5% and 18.4%, respectively. Thus, cultures resistant to SbIII from both clinical isolates were more resistant to complement-mediated lysis than drug-sensitive cultures SbIII resistant cultures also showed greater in vitro virulence on murine macrophages when compared to the corresponding sensitive cultures. The infection rate determined for sensitive and resistant SbIII AF was 260 and 593. For sensitive and resistant SbIII JCTS was 115 and 207, respectively. In the model of infection in vivo in swiss mice, no significant virulence was evident in any culture of L. braziliensis. Thus, we conclude that there is a correlation between parameters of in vitro virulence and resistance to SbIII in L. braziliensis.